The importance of the lexicon in establishing the concept of citizenship - Otaifi, Amr Ahmed (Arab Journal for Sciences and Research Publishing, 2016)
The study aimed at uncovering the role of the lexicon in establishing the concept of citizenship. Where two methods of contemporary language courses were used: The descriptive approach by describing the manifestations of the lexicon of the principles that fuel the feelings of national belonging among the people of the language. The second is lexical criticism. The research consists of two chapters: the first is the definition of significance in the Arabic dictionary, the second is the term of citizenship, its origin and meaning, and the third is the requirements of the new lexicon. And the second section of the homeland and citizenship in the contemporary and basic, and includes the demands of four: the first root (و ط ن), the second - the terms of common terminology, and the third - the formulation of the definition in the lexicons, and IV - supporting examples of citizenship. The study concluded that the studied lexicons contain many information with a national flavor, although one of them is not present in the previous dictionaries, with a clear effort, in which the modern lexicological industries are realized and the meaning of the fact that the individual belongs to one country without another and has his loyalty on the other , As well as the existence of educational inputs related to participation and real effectiveness.